2017
DOI: 10.1088/1674-1056/26/3/039401
|View full text |Cite
|
Sign up to set email alerts
|

The interaction between stratospheric monthly mean regional winds and sporadic-E

Abstract: In the present study, a statistical investigation is carried out to explore whether there is a relationship between the critical frequency (foEs) of the sporadic-E layer that is occasionally seen on the E region of the ionosphere and the quasibiennial oscillation (QBO) that flows in the east-west direction in the equatorial stratosphere. Multiple regression model as a statistical tool was used to determine the relationship between variables. In this model, the stationarity of the variables (foEs and QBO) was f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…In addition, it is also seen that both the eastern and western directions of the QBO are effective on current densities as positive. Similarly, in examinations made between the QBO and ionospheric parameters; it was reported that QBO was related in TEC (0.704) (Tang et al, 2015), between foF2 (0.64) (Chen, 1992); with foE 0.50 (Atıcı and Sagir); with foEs (between 0.58-0.94 range) (Cetin et al, 2017). In addition, Sagir et al (2015) reported a positive relation between the directions of the QBO and NnD.…”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation
“…In addition, it is also seen that both the eastern and western directions of the QBO are effective on current densities as positive. Similarly, in examinations made between the QBO and ionospheric parameters; it was reported that QBO was related in TEC (0.704) (Tang et al, 2015), between foF2 (0.64) (Chen, 1992); with foE 0.50 (Atıcı and Sagir); with foEs (between 0.58-0.94 range) (Cetin et al, 2017). In addition, Sagir et al (2015) reported a positive relation between the directions of the QBO and NnD.…”
Section: Resultsmentioning
confidence: 84%
“…It is known that Stratospheric QBO affects the ionosphere especially on the equatorial region [5,6,8,[10][11][12][13][14]. In the present study, the relation of QBO with the current density of the E-region of the ionosphere, which has a significant impact on satellite positioning, space weather forecast, and radio wave propagation were examined.…”
Section: Conclusion and Suggestionmentioning
confidence: 98%
“…Araştırma Makalesi/ Research Article MSU J. of Sci., 10:2 977-991, 2022 DOI: https://doi.org/10.18586/msufbd.1176184 ARIMA, machine learning, deep learning, experimental orthogonal analysis [1][2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…It is generally recognized that middle‐ and low‐latitude E s formation is attributed to meteor debris and neutral wind dynamics in mesosphere and lower thermosphere (MLT) region, which is an important transition zone of the coupling between ionosphere and low atmosphere (Mathews, ; Whitehead, ). E s is closely related to atmospheric waves with different scales, such as atmospheric gravity waves (Woodman et al, ), tidal waves (e.g., Haldoupis et al, ; Zhou et al, ), planetary waves (PWs; e.g., Haldoupis & Pancheva, ; Pancheva et al, ), Quasi‐Biennial Oscillation (Çetin et al, ), and even El Niño–Southern Oscillation (Chang et al, ).…”
Section: Introductionmentioning
confidence: 99%